Gallic Acid Ameliorates Angiotensin II-Induced Atrial Fibrillation by Inhibiting Immunoproteasome- Mediated PTEN Degradation in Mice - Han, Dan; Zhang, Qi-Yu; Zhang, Yun-Long; Han, Xiao; Guo, Shu-Bin; Teng, Fei; Yan, Xiao; Li, Hui-Hua (Frontiers in Cell and Developmental Biology, 2020)
Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia and is a major cause of stroke and heart failure. We and others have found that gallic acid (GA) plays a beneficial role in cardiac hypertrophic remodeling and hypertension. However, the effect of GA on angiotensin II (Ang II)-induced AF and atrial remodeling as well as the underlying mechanisms remain unknown. AF was induced in mice by Ang II infusion (2000 ng/kg/min) for 3 weeks. Blood pressure was measured using the tail-cuff method. Atrial volume was evaluated by echocardiography. Atrial remodeling was studied using hematoxylin and eosin, Masson’s trichrome, and immunohistochemical staining. Atrial oxidative stress was assessed by dihydroethidium staining. The gene expression of fibrotic and inflammatory markers and protein levels of signaling mediators were measured by quantitative real-time PCR and western blot analysis. In mice, GA administration significantly attenuated Ang II-induced elevation of blood pressure, AF incidence and duration, atrial dilation, fibrosis, inflammation, and oxidative stress compared with the vehicle control. Furthermore, GA downregulated Ang II-induced activity and expression of immunoproteasome subunits (β2i and β5i), which reduced PTEN degradation and led to the inactivation of AKT1 and downstream signaling mediators. Importantly, blocking PTEN activity by VO-Ohpic markedly reversed the GA-mediated protective effects on Ang II-induced AF and atrial remodeling. Therefore, our results provide novel evidence that GA exerts a cardioprotective role by inhibiting immunoproteasome activity, which attenuates PTEN degradation and activation of downstream signaling, and may represent a promising candidate for treating hypertensive AF.